Child Abuse Reporting Barriers: Iranian Nurses’ Experiences - Borimnejad, Leili (Iran Red Crescent Med J, 2015)
BACKGROUND: Although in many countries child abuse reporting is mandated, Iranian nurses report abused cases voluntary. Some of the cases are reported to the police and others are referred to welfare organizations or other non-governmental organizations. Absence of a uniform reporting system along with a lack of legal support in the specific cultural context of Iran has resulted challenges for the reporters of child abuse. OBJECTIVES: The aim of this study was to explore the Iranian nurses’ experiences of reporting child abuse as well as to explore the existing barriers. PATIENTS AND METHODS: A qualitative study with conventional content analysis was conducted to explore the barriers of reporting child abuse. Individual interviews between 30 and 45 minutes in duration were conducted with a purposive sample of 16 nurses with direct experience of dealing with children who had been abused. Graneheim and Lundman’s method was used for data analysis. RESULTS: The data were classified to five themes including “knowledge deficit”, “previous unpleasant experiences about child abuse reporting”, “ethical challenges”,” legal challenges” and “cultural beliefs”. CONCLUSIONS: According to the findings, enhancement of nurses and public knowledge about child abuse, legal issues and jurisprudence along with legislation of clear and simple laws, are mandatory to protect abused children in Iran.